The Use of Digital Library to Increase Students’ Reading Interest and Learning Independence - Sumardi, Sumardi (Basic and Applied Education Research Journal, 2023)
A digital library is a library in which the entire collections and the management process and services are in the form of digital. The digital library collection is not only limited to print-substitute electronic documents, but the scope of the collection extends to digital artifacts that cannot be replaced in printed form. In the context of learning media, digital libraries can function to provide a variety of textual documents, audio, images, and videos. With the enhancement of digital library management and services, it will certainly provide more excellent service to its users and will create a joyful experience while accessing various information in the library and thus, can invite many people to know more about digital libraries. Therefore, this digital library can influence students' reading interests as well as increase their learning independence. The method used in this research is a descriptive qualitative research method. It is a kind of method that creates a factual and accurate description of the facts, characteristics, and relationships that occur between one phenomenon and another being studied. The purpose of this research is to find out what factors that influence students' low interest in reading and their learning independence and how to use digital libraries to increase student’s reading interest and learning independence.